Exploring reasons for the weekend effect in a hospital emergency department: An information processing perspective - Iben Duvald (Journal of Organization Design, 2019)
This study examines fits and misfits between information processing requirements and capacities in a hospital emergency department in order to identify possible explanations for the "weekend effect." Previous research has shown that acute patients admitted to hospital emergency departments on a weekend experience, on average, worse outcomes than those admitted on a weekday. Why the weekend effect exists remains unclear. Based on an ethnographic field study conducted in an emergency department and by applying an information processing perspective, my findings indicate multiple changes in the organizational design that leads to substantial misfits which appears to be an explanation to why the quality of care provided by the emergency department differs on weekdays and weekends. The findings provide a new and more nuanced perspective on the causes of the weekend effect by investigating the setting in which patient care is delivered, and how it varies between weekdays and weekends.
Keywords: 650; Information processing perspective; Organizational fits and misfits; Organizational design; Hospital emergency department; Weekend effect